2002
DOI: 10.1021/jf011496m
|View full text |Cite
|
Sign up to set email alerts
|

Sulfometuron Incorporation in Cationic Micelles Adsorbed on Montmorillonite

Abstract: The aim of this study was to understand the interactions between alkylammonium cations present as monomers and micelles and a clay mineral, montmorillonite, to develop slow release formulations of anionic herbicides, such as sulfometuron (SFM) whose leaching in soils is an environmental and economic problem. In the proposed formulation the herbicide is incorporated in positively charged micelles of quaternary amine cations, which in turn adsorb on the negatively charged clay. The adsorption of hexadecyltrimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
64
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 29 publications
11
64
0
Order By: Relevance
“…The adsorbed mass increases with surfactant concentrations and eventually reaches a plateau when the CTMAB equilibrium concentration in water is approximately equal to the CMC (about 250 μg/mL). The isotherm is distinctly nonlinear and exhibits the characteristics of an L-type curve as previously reported (Lee et al 2000;Rosen and Li 2001;Mishael et al 2002;Zhu et al 2003). The sharpest curvature on the isotherm occurs at an aqueous concentration close to the CMC.…”
Section: Sorption Of Ctmab On Bentonitesupporting
confidence: 70%
See 1 more Smart Citation
“…The adsorbed mass increases with surfactant concentrations and eventually reaches a plateau when the CTMAB equilibrium concentration in water is approximately equal to the CMC (about 250 μg/mL). The isotherm is distinctly nonlinear and exhibits the characteristics of an L-type curve as previously reported (Lee et al 2000;Rosen and Li 2001;Mishael et al 2002;Zhu et al 2003). The sharpest curvature on the isotherm occurs at an aqueous concentration close to the CMC.…”
Section: Sorption Of Ctmab On Bentonitesupporting
confidence: 70%
“…Depending on the net effect of these two processes, the apparent solute solid-water distribution coefficient (K d *) in a mixture containing surfactant may increase or decrease relative to the intrinsic distribution coefficient (K d ) of the same solute without surfactant. At low CTMAB concentrations, CTMAB is sorbed preferentially by cation exchange onto the solid surface to form an "adsorbed film," and then further sorption at high CTMAB concentrations creates a partition-like medium, which may be viewed as a surface-micelle phase (Mishael et al 2002;Polubesova et al 2005). The alternate explanation for our results is that some enhancement of pesticide sorption on bentonite is due to the formation of such thin film by adsorption of CTMAB, whereas there is also enhancement due to binding of the pesticides to the surface-micelle phase.…”
Section: Sorption Of Ctmab On Bentonitementioning
confidence: 99%
“…The interpretation of this outcome might be that initially a large fraction of the desorbed herbicide is due to relatively more loosely bound molecules. For instance, in (16) we found that a few percent of the adsorbed SFM arises from direct SFM adsorption on the ODTMA-clay mineral, which might be positively charged by adsorption of ODTMA monomers above the cation exchange capacity.…”
Section: Resultsmentioning
confidence: 92%
“…The formulations are based on SFM incorporated in positively charged quaternary amine cation micelles, which are adsorbed on a negatively charged clay mineral, montmorillonite. Anionic herbicides such as SFM do not adsorb directly on the clay mineral (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation